면역억제능을 보유한 地楡의 인슐린 분비능 연구 - 황석연(Seock Yeon Hwang); 김명현(Myung Hyun Kim); 강정수(Jung Soo Kang); 김병수(Byoung Soo Kim) (동의생리병리학회지, 2014)
Immunosuppressors cyclosporine A(CsA) and tacrolimus(FK506), the primary cellular target of which is calcineurin/nuclear factor of activated T cells(NFAT) signalling pathways, decrease beta-cell insulin content and mRNA expression. The posttransplantation diabetes mellitus(PTDM) is a frequent complication in immunosuppressive therapy. The present study was to examine the effect of a crude water extracts of medicinal herbs such as Sanguisorba officinalis(SOE) on the immunosuppressive activity with lymphocyte and insulin secretion in insulinoma cell lines with RIN-5mF. It was found that SOE treatment had effect of immunosuppressor on lymphocytes and also significantly increased insulin secretion in RIN-5mF compared to other agents. we might suggest a mechanism on insulin secretion by HNF4a. Taken together, the present study suggested that SOE might serve as immunosuppressive drug in PTDM. KCI Citation Count: 1